2014
DOI: 10.9734/ijtdh/2014/5041
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium Levels in Women with Breast Cancer in Benin City, Nigeria

Abstract: Aim:The aim of this study was to compare the serum magnesium levels of patients with breast cancer and apparently healthy people without the disease. Study Design: This is a cross-sectional prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
3
1
Order By: Relevance
“…In the present study, magnesium was deficient in 42% of the patients with breast cancer and in 5% of the control group. Magnesium levels were significantly lower in the breast cancer group (p<0.001), which is in agreement with Sartori et al [23] and Atoe et al [22], which suggests that serum Mg was significantly lower in the patients with breast cancer compared to the control group and contradictory to the findings by Arinola et al [28] who reported slight hypomagnesaemia in patients with breast cancer. Abdelgawad et al [29] found no significant difference when comparing Mg levels between the breast cancer and the control group.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, magnesium was deficient in 42% of the patients with breast cancer and in 5% of the control group. Magnesium levels were significantly lower in the breast cancer group (p<0.001), which is in agreement with Sartori et al [23] and Atoe et al [22], which suggests that serum Mg was significantly lower in the patients with breast cancer compared to the control group and contradictory to the findings by Arinola et al [28] who reported slight hypomagnesaemia in patients with breast cancer. Abdelgawad et al [29] found no significant difference when comparing Mg levels between the breast cancer and the control group.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, ALP and calcium showed a non-significant rise in non-metastatic cases and registered a significant rise (p<0.001) in metastatic patients, respectively, which is consistent with the findings of Uemura et al [20] and Mulholland et al [21] which indicate no significant difference in ALP levels in non-metastatic breast cancer. Atoe et al [22] revealed a significant rise in ALP and calcium in metastasis and no change in non-metastatic groups, which suggested the involvement of bone in cancer metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…Serum Mg levels in this study were statistically not different in the control and CIN groups evaluated. This observation is different from the report from a study to compare serum Mg levels in women with breast cancer in Benin City, Nigeria (Atoe et al, 2014). In the just mentioned study, results showed a significant reduction in serum Mg levels of patients with breast cancer compared with those without the disease.…”
Section: Atoe K; Peter Oocontrasting
confidence: 89%
“…Results similar to our study were observed in study conducted by researchers Atoe et al, in 2014 in Nigeria. They demonstrated that serum Mg levels were lower in Breast Cancer patients as compared to healthy controls [17].…”
Section: Discussionmentioning
confidence: 99%